The Benefits of Black Garlic to Human Health - Sema Özmert Ergin (Turkish Journal of Agriculture: Food Science and Technology)
Garlic (Allium sativum L.) is a vegetable that is known to be medically beneficial and has been around since the past in the world cuisine. The unique taste and smell of garlic affects its raw consumption negatively. One of the functional uses of garlic, ‘black garlic’ is produced by fermenting white garlic under certain temperature and humidity conditions. Thus, the bitter taste and smell of garlic disappears and also changes occur in its nutritional value. Studies show that black garlic has anticancer, antitumor, antiallergic and antimicrobial effects. It also plays protective and therapeutic role against diabetes, obesity, cardiovascular diseases. This product, which is new for many countries, is not well known and consumed in our country too. In this study, the bioavailability of black garlic was highlighted and information was given about its production and antioxidant activity.